2008
DOI: 10.1007/s11199-008-9543-y
|View full text |Cite
|
Sign up to set email alerts
|

Gender Role Self-Concept and Leisure Activities of Adolescents

Abstract: The present study investigated the relevance of gender role self-concept to leisure activities of female and male adolescents. A sample of 310 Austrian adolescents (14 to 16 years old) participated in the study. Gender role self-concept was measured based upon a multi-dimensional conceptualization that includes positive and negative selfdescriptions. Gender role self-concept significantly predicted female-typed and male-typed leisure activities in addition to participants' gender and partially mediated the lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 26 publications
3
26
0
6
Order By: Relevance
“…At the same time, electronic media played an important role in teenagers' leisure time and relational activities, with results consistent with those of previous studies presented above (e.g. Athenstaedt et al 2009;EGM Baròmetre 2014;Bell and Dittmar 2011;Coatsworth et al 2005;Fernández-Planells and FiguerasMaz 2012;Funes 2008;Holloway and Green 2008;Livingstone et al 2011;Roberts and Foehr 2008;Romer et al 2012;Videnovic´ et al 2010). In particular, the computer connected to the Internet represents the pillar of teenagers' personal media equipment.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…At the same time, electronic media played an important role in teenagers' leisure time and relational activities, with results consistent with those of previous studies presented above (e.g. Athenstaedt et al 2009;EGM Baròmetre 2014;Bell and Dittmar 2011;Coatsworth et al 2005;Fernández-Planells and FiguerasMaz 2012;Funes 2008;Holloway and Green 2008;Livingstone et al 2011;Roberts and Foehr 2008;Romer et al 2012;Videnovic´ et al 2010). In particular, the computer connected to the Internet represents the pillar of teenagers' personal media equipment.…”
Section: Discussionsupporting
confidence: 89%
“…In fact, more recent works, carried out since the last years of the 1990s, have identified the main features of youth's media and leisure habits, emphasizing in particular their use of new media (e.g., Athenstaedt et al 2009;Bell and Dittmar 2011;Coatsworth et al 2005;Hagen 2007;Holloway and Green 2008;Livingstone et al 2011;Pascoe 2011;Roberts and Foehr 2008;Romer et al 2012;Thulin and Vilhelmson 2007;Videnovic´ et al 2010;Wilska and Pedrozo 2007).…”
Section: Young People's Media Usage and Leisure Preferencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, differences in leisure experiences may be affected by the adolescent's gender. Various studies have shown strong gender differences in adolescents' choices and preferences in leisure activity participation [29][30][31][32][33][34]. Girls have been found to be more involved than boys in individual sports and creative activities such as dancing, music, and drama, whereas boys have been found to spend more time than girls on team sport activities and computerrelated activities [30,32,[35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…In the academic field, it is known that academic self-concept is part of self-concept [20], where there are differences in academic self-concept between male and female students [21], [22]. Self-concept also provides a difference in perceived emotion [23], [24], in which mood is happy or sadly very influential [25] towards the direction of both male and female activities [26]. In adolescence or at school in secondary education, emotional factors are very influential in the period of development of selfconcept [27], [28].…”
Section: Introductionmentioning
confidence: 99%